Transforming the English model of community safety: From crime and disorder to the safeguarding of vulnerable people - Menichelli, Francesca (Criminology & criminal justice, 2020)
The literature on the English model of community safety describes it as being centrally directed, situational in nature, focused on anti-social behaviour and incivilities and not concerned with measures of social crime prevention. Based on an analysis of the community safety plans issued by English and Welsh local authorities between 2010 and 2014, this article argues that such a characterization is no longer accurate. Partnerships in England and Wales are now free from central oversight, and increasingly focused on safeguarding. In light of the work they do in support of vulnerable populations, and their role within the changing governance of England, more attention should be paid to them.